Organization of Distance Learning in School, College, University - N. V. Nikulicheva; O. I. Dyakova; O. S. Glukhovskaya (Открытое образование (Москва), 2020)
The purpose of research is to study and illustrate the main stages of implementing distance learning (DL) in schools, colleges, and universities using examples of real educational organizations. Materials for the study were the results of the authors’ work on the implementation of DL in the educational process of their organizations. The methodological work was based on the DL theoretical foundations of E.S. Polat scientific school and her followers. To achieve this goal and solve problems, the following groups of research methods were used:– theoretical: analysis of psychological, pedagogical, methodological literature, regulatory documents in the aspect of the problem under study; modeling of distance learning in educational organizations, systematization of scientific and theoretical and experimental data; classification of selected components and characteristics;– empirical-diagnostic (survey); observational (observation-direct and indirect, long and short-term);– statistical: measurement of the obtained data (collection of statistical material); determination and processing of quantitative and qualitative indicators of the experiment.The theory and practice of DL in Russia has been going on for over 20 years. When implementing DL in an educational organization, it is important to study the main concepts of DL in Russian and foreign scientific schools, determine the implementation strategy, but not to act “blindly”. A huge problem comes to the fore: the lack of readiness of the teaching staff to comprehend and master modern pedagogical and information technologies for organizing the distance learning process. The absence of the development concept of a pedagogical system for the majority of heads of educational organizations allows for some confusion in the submission and control of educational material, the process is aggravated by the lack of full-fledged consultations, as a result of which many participants in the educational process are dissatisfied with the results. Instead of the stage of serious system design, lecturers limit themselves to digitizing ready-made traditional lectures, conducting them in the “talking head” mode with reading the theory from the screen, introducing an automated testing system or any number of tasks “from the textbook” with the message “send a photo of the completed task”, which, of course, cannot lead to a high-quality learning process. Most lecturers try to transfer all the elements of the full-time learning system to the distance learning system automatically when changing the form of training, which is basically impossible when changing the environment. The new learning environment has different capabilities and requires the lecturer to plan differently, present information, and organize monitoring and record results.The results of the study allowed us to identify general trends in the organization of DL at all levels of education and specific problems typical for particular levels. The main issue in organization DL at school was the creation of the learning environment (technical support, Internet, organization of DL pedagogical system) as well as methodological support of DL process (training lecturers in DL methodology). In higher education institutions and colleges, the main problem turned out to be stimulating the teaching staff to master the methodological and technical foundations of DL, since the majority of lecturers clearly lacked motivation to provide a high-quality DL. In conclusion, it should be noted that for further development of distance learning, the management of organizations needs to think about developing economic mechanisms for paying developers of distance learning courses and lecturers, working out copyright protection for created distance learning courses, training lecturers in the methodology for developing and conducting distance learning courses, purchasing professional DLS (distance learning systems) with a guarantee of technical support from developers for several years and customization for the needs of the organization. There is also a need for a system of benefits and incentives for distance lecturers on health protection and incentives for further high-quality work.